Metal-free photo-induced heteroarylations of C–H and C–C bonds of alcohols by flow chemistry. Issue 11 (18th May 2022) - Cao, Zhu; Ji, Meishan; Wang, Xinxin; Wu, Xinxin; Li, Yahong; Zhu, Chen
Abstract : Practical, metal-free heteroarylations of inert C–H and C–C bonds of unprotected aliphatic alcohols are achieved in a 'stop-flow' micro-tubing reactor, and can be readily scaled up by a continuous-flow method. Abstract : Practical, metal-free heteroarylations of C–H and C–C bonds of unprotected aliphatic alcohols are accomplished in a 'stop-flow' micro-tubing reactor. The reactions proceed through alkoxy radical-triggered hydrogen atom transfer and β-C(sp 3 )–C(sp 3 ) bond rupture under mild photochemical conditions, leading to a plethora of valuable functionalized heteroarenes. The reaction is amenable for late-stage functionalization of complex heteroarenes, and can be readily scaled up by a continuous-flow method. The protocol features many advantages including good regioselectivity, broad functional group compatibility, and easy operation, and may find potential use in medicinal chemistry.